2021
DOI: 10.1007/s11136-021-02935-w
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Health Quality of Life Questionnaire (MHQoL): development and first psychometric evaluation of a new measure to assess quality of life in people with mental health problems

Abstract: Purpose The purpose of this study was to develop and psychometrically evaluate a new quality of life measure for use in people with mental health problems—the Mental Health Quality of Life questionnaire (MHQoL). Methods The MHQoL dimensions were based on prior research by Connell and colleagues, highlighting the seven most important quality of life dimensions in the context of mental health. Items were generated following a systematic review we performed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…In an attempt to overcome this problem, the Mental Health Quality of Life instrument (MHQoL) was developed [ 9 ]. The MHQoL is a self-report, seven-item questionnaire that captures and values dimensions relevant to the quality of life of people with mental health problems, such as self-image, independence and hope.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an attempt to overcome this problem, the Mental Health Quality of Life instrument (MHQoL) was developed [ 9 ]. The MHQoL is a self-report, seven-item questionnaire that captures and values dimensions relevant to the quality of life of people with mental health problems, such as self-image, independence and hope.…”
Section: Introductionmentioning
confidence: 99%
“…This is even more important if healthcare decisions are informed by economic evaluations using the MHQoL as outcome measure. The psychometric properties of the MHQoL so far have only been examined in the Dutch context [ 9 ]. This evaluation was performed in a sample of 110 members of the Dutch general public as well as a sample of 479 Dutch mental healthcare users.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Soeteman et al [244] concluded that the EQ-5D is sensitive to changes in the health status of patients with cluster B personality disorders. In addition to the EQ-5D, quality of life will be assessed by a recently developed instrument specially developed for patients with mental health problems (MHQoL-7D; [197]). The validation of this instrument is currently in progress, but preliminary results are promising [197].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the EQ-5D, quality of life will be assessed by a recently developed instrument specially developed for patients with mental health problems (MHQoL-7D; [197]). The validation of this instrument is currently in progress, but preliminary results are promising [197]. Another point for consideration is that conclusions with regard to the most cost-effective treatment choice can be affected by the amount the society is willing to pay for an additional unit of effectiveness (i.e., willingness-to-pay threshold).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation